How a working day‐induced‐tiredness may alter some facial signs in differently‐aged Caucasian women. (29th May 2017) - Flament, F.; Pierre, J.; Delhommeau, K.; Adam, A. S.
Abstract: Objectives: To assess the alterations of some facial clinical signs after a working day in French Caucasian women. Methods: Standardized photographs of full faces of 111 women of two different age classes were taken before and after a working day. Photos were submitted in blind (morning or evening) to a panel of 10 experts for scoring the severity of eight different facial signs using specific scales as established by previously published referential skin atlases. A panel of 60 naïve women gave their assessment of the overall look (more or less tired, aged, dull) from paired (morning/evening) photos given in blind. Subjects under study were asked to fill a questionnaire about their perceived state of tiredness before and after a normal working day. Results: All subjects felt a little more tired at evening although, surprisingly a little less in the older group (55–65 year) than their younger counterparts (25–35 year). Both groups were judged slightly less 'young' and 'more tired' at evening by the assessment panel, whereas the dull aspect remained unaltered. Four facial signs, among the 8 scored, showed subtle but significant changes, according to age class. Among older women, eye bags improved at evening as compared to morning, whereas glabellar wrinkles were found slightly accentuated. In younger subjects, nasolabial fold and crow's feet wrinkles were found of an aggravated severity score. Conclusion: A normal working day induces, in the studied women, slight but detectable changes in some facial signs that vary (location, intensity) according to age. Abstract : Illustration of morning‐evening maximal changes in two facial signs in both age‐classes.